Assessment of Water Ecological Carrying Capacity based on Ecological Network Structure - Hairet, Turson; Wang, Weilong; Li, Yuan; Li, Shengsheng (Journal of Environmental Accounting and Management, 2026)
In this study, ecological network structure analysis is applied into water ecological carrying capacity assessment. Based on theory of ecological network analysis in sustainability quantification and the relationship of WECC and sustainable water use, with the application of presumed water use network model and a new index, WECC is measured from integrated perspective with Baiyang Lake Basin as a case study. The result suggests that with a distance of 28.33×108 m3 network throughflow from that of sustainable network, the network structure is unbalanced. It means that for Baiyang Lake Basin in 2007, the water use network cannot carry throughputs in a sustainable way and its overload quantity is 28.33×108 m3. Through adjusting throughflow on each pathway toward network structure balancing, this method could provide a scientific basis for the coordinated development of social economy and the water eco-environment improvement in the Baiyang Lake Basin.